Lack of nAChR activity depresses cochlear maturation and up-regulates GABA system components: temporal profiling of gene expression in alpha9 null mice. - Sevin Turcan; Donna K Slonim; Douglas E Vetter (PLoS ONE)
Background It has previously been shown that deletion of chrna9, the gene encoding the alpha9 nicotinic acetylcholine receptor (nAChR) subunit, results in abnormal synaptic terminal structure. Additionally, all nAChR-mediated cochlear activity is lost, as characterized by a failure of the descending efferent system to suppress cochlear responses to sound. In an effort to characterize the molecular mechanisms underlying the structural and functional consequences following loss of alpha9 subunit expression, we performed whole-transcriptome gene expression analyses on cochleae of wild type and alpha9 knockout (alpha9(-/-)) mice during postnatal days spanning critical periods of synapse formation and maturation. Principal findings Data revealed that loss of alpha9 receptor subunit expression leads to an up-regulation of genes involved in synaptic transmission and ion channel activity. Unexpectedly, loss of alpha9 receptor subunit expression also resulted in an increased expression of genes encoding GABA receptor subunits and the GABA synthetic enzyme, glutamic acid decarboxylase. These data suggest the existence of a previously unrecognized association between the nicotinic cholinergic and GABAergic systems in the cochlea. Computational analyses have highlighted differential expression of several gene sets upon loss of nicotinic cholinergic activity in the cochlea. Time-series analysis of whole transcriptome patterns, represented as self-organizing maps, revealed a disparate pattern of gene expression between alpha9(-/-) and wild type cochleae at the onset of hearing (P13), with knockout samples resembling immature postnatal ages. Conclusions We have taken a systems biology approach to provide insight into molecular programs influenced by the loss of nicotinic receptor-based cholinergic activity in the cochlea and to identify candidate genes that may be involved in nicotinic cholinergic synapse formation, stabilization or function within the inner ear. Additionally, our data indicate a change in the GABAergic system upon loss of alpha9 nicotinic receptor subunit within the cochlea.